The Estimation of the Importance of Universities Performance Assessment for Stakeholders - Tikhonova, Anna Dmitrievna (Economy of Regions, 2018)
The issue to assess the activity of universities by the various interested parties (stakeholders) is relevant. It is caused by the reforming processes of higher education regarding the transformation of institutions into entities of special type. These entities are able to meet the needs of labour market applying lifelong learning according to the requirements of enterprises to realize the intellectual potential in industries of the country. The research includes the analysis of the existing definitions of the term “education service” and criteria for universities performance assessment used in various ratings. I have conducted a survey, which is based on the collection of data from students, graduates, university entrants, industrial leaders and other potential employers as key stakeholders. The opinion of these stakeholders should be considered by universities when planning a strategy to improve their activity. I wondered whether preferences for characteristics of universities differ for the representatives of various groups of stakeholders or not. The research results have showed that preferences of both the representatives of business and the society, in general, have the same direction, though by a number of criteria they significantly differ. As a result of the analysis, I have developed a model for defining a programme of actions, which increase those performance indicators, which are significant for the main stakeholders of the education market. Therefore, the increase in universities performance finally will contribute to the socio-economic development of regions. The research results can be applied to eliminate a number of controversial issues concerning the requirement for universities to process a strategic potential to address major problems of innovative development of the country.